Homolog pairing and sister chromatid cohesion in heterochromatin in Drosophila male meiosis I. - Tsai, J.H.; Yan, R.; McKee, B.D. (Chromosoma, 2011)
Drosophila males undergo meiosis without recombination or chiasmata but homologous chromosomes pair and disjoin regularly. The X-Y pair utilizes a specific repeated sequence within the heterochromatic ribosomal DNA blocks as a pairing site. No pairing sites have yet been identified for the autosomes. To search for such sites, we utilized probes targeting specific heterochromatic regions to assay heterochromatin pairing sequences and behavior in meiosis by fluorescence in situ hybridization (FISH). We found that the small fourth chromosome pairs at heterochromatic region 61 and associates with the X chromosome throughout prophase I. Homolog pairing of the fourth chromosome is disrupted when the homolog conjunction complex is perturbed by mutations in SNM or MNM. On the other hand, six tested heterochromatic regions of the major autosomes proved to be largely unpaired after early prophase I, suggesting that stable homolog pairing sites do not exist in heterochromatin of the major autosomes. Furthermore, FISH analysis revealed two distinct patterns of sister chromatid cohesion in heterochromatin: regions with stable cohesion and regions lacking cohesion. This suggests that meiotic sister chromatid cohesion is incomplete within heterochromatin and may occur at specific preferential sites.